The effect of containing Al2O3 microparticles in different matrix polymers on properties of pineapple fiber-reinforced composites - Indra, Mawardi; Hanif, Razak; Zaini, Akadir; Putra Jaya, Ramadhansyah (Italian Group of Fracture (IGF), 2024)
In this study, Al2O3 microparticle was used as a filler for pineapple fiber reinforced composites with different matrix polymers. The effect of Al2O3 microparticles in the epoxy and unsaturated polyester matrix on the mechanical, physical, and thermal properties of pineapple fiber reinforced composites was investigated. Pineapple fiber composite was manufactured by hand layup with various Al2O3 contents, 0, 5, 10, and 15 wt%, and a 30 wt% continuous pineapple fiber. The tensile, flexural strength, hardness, water absorption, and thermal stability were investigated according to ASTM. The results showed that flexural strength, hardness, density, and water resistance gradually increased, and the tensile strength rate gradually decreased with more the wt.% of Al2O3 microparticle. The TGA observation results indicated that the Al2O3 microparticles improved the composite's thermal stability. Composites with the epoxy matrix are superior in tensile strength and thermal stability compared to composites made of unsaturated polyester. In contrast, unsaturated polyester matrix composites had higher flexural strength, hardness, density, and water resistance than epoxy matrix composites. The effect of the content of 15 wt% Al2O3 microparticles in the composites resulted in the highest flexural strength, hardness, density, and water absorption resistance, while the tensile strength showed the lowest value.